Orphanhood and the Living Arrangements of Children in Sub-Saharan Africa - Beegle, Kathleen (2012)
Increasing adult mortality due to HIV/AIDS in Sub-Saharan Africa raises considerable concerns about the welfare of surviving children. Studies have found substantial variability across countries in the negative impacts of orphanhood on child health and education. One hypothesis for this variability is the resilience of the extended family network in some countries to care for orphans-networks under increasing pressure by the sheer number of orphans in many settings. Using household survey data from 21 countries in Africa, this study examines trends in orphanhood and living arrangements, and the links between the two. The findings confirm that orphanhood is increasing, although not all countries are experiencing rapid rises. In many countries, there has been a shift toward grandparents taking on increased childcare responsibility-especially where orphan rates are growing rapidly. This suggests some merit to the claim that the extended network is narrowing, focusing on grandparents who are older and may be less able to financially support orphans than working-age adults. However there are also changes in childcare patterns in countries with stable orphan rates or low HIV prevalence. This suggests future work on living arrangements should not exclude low HIV/AIDS prevalence countries, and explanations for changes should include a broader set of factors.